The Influence of Social Media Marketing Activities, Brand Equity, and Celebrity Endorsement on Purchase Intention for Coffee Beverages on Instagram - siti mariam; Hauzan Afif Prakoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
In today's era of globalization, business competition to attract consumer purchase interest has intensified, particularly among coffee beverage products on social media. This study was conducted to examine the influence of Social Media Marketing Activities, Brand Equity, Celebrity Endorsement on Purchase Intention for Fore Coffee products on Instagram. This research uses a quantitative method with SPSS software. The respondents in this study are consumers who have consumed beverages from Fore Coffee at least twice in the past month, with a total of 115 respondents. The data collection technique used in this study was a questionnaire distributed via Google Form. The results of this study found that Social Media Marketing Activities have a positive and significant influence on Purchase Intention, Brand Equity has a positive and significant influence on Purchase Intention, and Celebrity Endorsement also has a positive and significant influence on Purchase Intention. Furthermore, Social Media Marketing Activities, Brand Equity, and Celebrity Endorsement collectively have a positive and significant influence on Purchase Intention for Fore Coffee products on Instagram.